PERAN PHYSICAL SETTING DALAM INTERAKSI SOSIAL ANAK PADA AREA KOMUNAL DI RUSUNAWA - Aprilia Anggraeni Putri (Ide dan Dialog Desain Indonesia (Idealog), 2018)
In 2015, Indonesia was faced with the high relocation intensity of dense settlements into flats. As a result, various community groups experience changes in the environment, especially children who have to face an immediate environment in the flat. One aspect of life that is affected is the social aspect which is closely related to the communal area in the flat environment. The communal area, which acts as a place for children's social interaction, consists of the physical settings and activities that exist in the area. Both influence each other. The different physical settings in a social space can cause differences in opportunities for children's social interaction. This study aims to examine the role of physical setting of the communal area towards children's social interactions that occur. The research method is qualitative with a case study approach. Observations and interviews were carried out as data collection techniques for later descriptive analysis phase. The results showed that physical settings affect how children choose areas for their interaction activities. Limits to freedom of interaction and feelings of isolation also arise due to physical limitations on physical settings of communal areas in flat towers which is influenced by the experience of children in their old environment. Keywords: children, communal area, physical setting, flat